Supporting the Implementation of Evidence-Based Behavior Management Practices through Simulation: A Mixed Method Study. Issue 4 (2nd October 2021) - Shernoff, Elisa S.; Frazier, Stacy L.; Lisetti, Christine; Delmarre, Alban; Bibi, Zainab; Gabbard, Joseph
ABSTRACT: Simulation training models, such as Interactive Virtual Training for Teachers (IVT-T), have relevance to consultation and show promise in supporting teachers who need behavior management support. Using an embedded mixedmethod design, we examined the feasibility and effectiveness of IVT-T. Twenty seven teachers working in three K-8 schools participated in the quantitative strand and 18 teachers participated in the qualitative strand. Training dosage data indicated many teachers used IVT-T but 62% were unable to meet the minimum dosage of 45 min per week. Instructional design issues, using the system outside school, and technical glitches may explain lower use. On average, use of several evidence-based strategies increased from pre to post while instructional design weaknesses related to storylines and phases of training may have impacted translation of practices to the classroom. Implications for consultation-based services are discussed along with future directions for our work.